RISK FACTORS ASSOCIATED WITH THE DEVELOPMENT OF HELLP SYNDROME IN PREGNANT WOMEN TREATED AT THE NATIONAL MATERNAL INSTITUTE PERINATAL, LIMA, 2018-2021: A CASE REPORT - Rojas-Vargas, Sofia (2024)
We present an unusual case of birth of a neonate with complex chromosomal rearrangement type apparently balanced three-way translocation, The neonate presented with karyotype 46, XY t(3; 12; 15)(q12; q13; q15) de novo, with dysmorphic features, such as low ear implantation, redundant skin on the neck , micropenis,  congenital heart disease with anatomical variant without functional alteration who was born and evaluated at our institution. This type of rearrangement is usually related to conditions other than congenital malformations, such as hematological disorders, and in phenotypically normal carriers with fertility problems; therefore, it is important to carry out a thorough follow-up of the patient due to possible complications in their psychomotor development and adequate genetic counseling to family members.